Analisis Self Reported Asuhan Persalinan oleh Lulusan DIII Kebidanan dan Medical Error An Analysis of Self Reported of Delivery Care by DIII Midwifery Graduates and Medical Error - istri bartini ova emilia adi utarini (Berita Kedokteran Masyarakat (BKM), 2011)
Background: Increased coverage of deliveries by health personnel in Indonesia (82.3%) does not synergize with decreased MMR (228/100.000 live births). The low quality of care at the primary level becomes the main causal factor for the slow achievement of the MDGs. Midwives as providers in the primary care level become the front liners in delivery assistance. Public perception of the low quality of DIII midwifery graduates  becomes a concern to the occurrence of medical errors by DIII midwifery graduates. Competence of delivery care is one of midwives’ competences at risk of medical error. In Bantul District, the number of maternal deaths in 2010 was 18 cases with a majority of deaths occurring during childbirth.Objective: To describe compliance to normal delivery care and medical errors that occurred in the delivery care conducted by DIII midwifery graduates.Methods: A quantitative study with a cross-sectional design to the occurrence of medical errors in delivery care by DIII midwifery graduates in Bantul District. Data were collected by questionnaire (self reported) and analyzed by univariate, bivariate and multivariate.Results: The results of the analysis suggested that 41.51% medical error occurred in the delivery care and 24.53% of delivery care by D III midwifery graduates were categorized as not good (n = 53). Self reported about medical errors in the four aspects being studied showed that 14 respondents (26.42%) said that medical error ever occurred in the action aspect of delivery assistance, 10 respondents (18.87%) said that medical errors occurred in the prevention of infection, 8 respondents (15.09%) stated that medical error occurred during the administration of drugs and only 3 respondents (5.66%) said that medical errors occurred at the time of diagnosis establishment. Not good delivery care was significant to the occurrence of medical errors (p = 0.000), and 3.8 times causing a medical error after being controlled by extraneous variables (facilities & SOP) with R² value of 0.16.Conclusion: Delivery care by DIII midwifery graduates in Bantul District 75,5% was categorized good, and 41.51% medical error occurred in the delivery care. The prevalence of not good delivery care increased the incidence of medical errors than that of good delivery care. Medical errors in delivery care expressed through self-reported in this study showed that they were also influenced by the completeness of equipment and standard operating procedures in obstetric care facility.Keywords: medical error, DIII Midwifery Graduates, delivery care